Risk factors for Post-operative Complications of Surgical Interventions done in Small Bowel Obstruction (SBO): A study of 100 cases (Bangladesh Critical Care Journal, 2021)
Background: Small bowel obstruction (SBO) is one of the most frequent indications for emergency surgery, and is known as a high-risk procedure with a morbidity and mortality rates at 20-30% and 3-5% respectively. Although it is a frequent surgery encountered in daily practice but less scientific work is noticed regarding this topic. The aim of the study was to identify the risk factors associated with various post-operative complications of different surgical interventions done for small bowel obstruction (SBO).Methods: This hospital based observational study was conducted at the department of surgery in Jahurul Islam Medical College Hospital, from January 2018 to June 2019. Patients undergoing surgery for SBO were included in the study. Informed consent was taken from all study subjects and ethical issues were ensured. Data were collected using a semi-structured questionnaire. Collected data were analyzed by the SPSS v22.Results: Out of 100 patients, 66% were male. Mean age was 47.46±13.46 years and prevalent (54%) age group was 41 – 60 years. The most common cause of acute small bowel obstruction was band and adhesion (38%), followed by obstructed hernia (30%), intestinal tuberculosis (15%), obstruction due to neoplasm (9%), intussusception (4%), Crohn’s disease (2%) and worm bolus (2%). During operation 78% patients had clear peritoneal content, 14% had hemorrhagic peritoneal content and 8% had purulent content. Condition of the gut was viable in 83%, reversibly ischemic and gangrenous bowel were present in 10% and 7% cases respectively. Most frequent complications were wound infection (14%) followed by post-operative ileus (6%) and basal atelectasis (6%). Delay in presentation was significantly associated with the development of post-operative complications (p